The impact of grandchild care provision on grandparents’ depressive symptoms across Europe using multi-level analysis: do the grandchild caring patterns and the country’s economy matter? - Yazhen Yang; Maria Evandrou; Athina Vlachantoni (Genus, 2022)
Abstract Little research has examined the cross-national differences in the impact of grandchild care provision on the grandparents’ depression, by taking into account of both macro- and micro-level factors. This study used a unique grandchild caring pattern variable in order to examine the effect of the changes in the intensity of grandchild caring on the grandparents’ depressive symptoms in European countries, and whether the grandparents’ country level economy influenced such effect. Longitudinal data derived from the Survey of Health, Ageing, and Retirement in Europe 2010–2018 covered 13 countries and 24,656 grandparents aged 50–90. Multi-level linear regression analyses with REML estimation were used. This study found that providing grandchild care had a protective effect against grandparents’ depressive symptoms in both lower and higher income countries. Moreover, providing more intensive grandchild care reduced the grandparents’ depressive symptoms to a greater extent in lower income countries than higher income countries. In addition, grandmothers benefited more from grandchild caring than grandfathers, and the gender gap in the effects of grandchild care provision on one’s depressive symptoms was wider in lower income countries than higher income countries in Europe. Future research can further investigate the mechanisms behind such results. The research findings can be used to develop targeted interventions aimed at grandparents providing childcare of different intensity.